Delineation of the Roles Played by RasG and RasC in cAMP-dependent Signal Transduction during the Early Development of Dictyostelium discoideum - Bolourani, Parvin (The American Society for Cell Biology, 2006)
On starvation, the cellular slime mold Dictyostelium discoideum initiates a program of development leading to formation of multicellular structures. The initial cell aggregation requires chemotaxis to cyclic AMP (cAMP) and relay of the cAMP signal by the activation of adenylyl cyclase (ACA), and it has been shown previously that the Ras protein RasC is involved in both processes. Insertional inactivation of the rasG gene resulted in delayed aggregation and a partial inhibition of early gene expression, suggesting that RasG also has a role in early development. Both chemotaxis and ACA activation were reduced in the rasG(−) cells, but the effect on chemotaxis was more pronounced. When the responses of rasG(−) cells to cAMP were compared with the responses of rasC(−) and rasC(−)rasG(−) strains, generated in otherwise isogenic backgrounds, these studies revealed that signal transduction through RasG is more important in chemotaxis and early gene expression, but that signal transduction through RasC is more important in ACA activation. Because the loss of either of the two Ras proteins alone did not result in a total loss of signal output down either of the branches of the cAMP signal-response pathway, there appears to be some overlap of function.